Material response and failure of highly deformable carbon fiber composite shells. (20th October 2020) - Schlothauer, Arthur; Pappas, Georgios A.; Ermanni, Paolo
Abstract: Very thin carbon fiber composite shells can withstand large bending curvatures without failure. The resulting high tensile and compressive strains require accurate modeling of the fiber-dominated non-linear effects to predict the mechanical response. To date, no universal modeling technique can precisely capture the behavior of such structures. In this work, successful representation of composite's response was achieved by utilizing single fiber tension and compression experimental data, implemented to extend a basal-plane-realignment based non-linear carbon fiber material model. Numerical techniques were adopted to model the bending behavior of unidirectional carbon fiber composites that was recorded in a comprehensive experimental campaign. Observations show that high material non-linearity leads to a non-negligible neutral-axis shift and drastic reduction of bending modulus due to compressive softening. Tensile fiber failure is the driving mechanism in thin shells flexure allowing for elastic compressive strains of up to 3% without micro-buckling. As a result, a remarkable flexibility in thin shells is realized. With increasing thickness, the elastic flexibility is reduced as the failure-driving mode switches to compressive micro-buckling. Graphical abstract: